A Critique of Risk Disclosure as the Solution for Minimizing Toxic Exposures in Pregnancy: The Case of Nail Salon Workers. (May 2017) - Ford, Anne Rochon; Scott, Dayna Nadine
The issue of pregnant women's exposures to everyday chemicals and the implications for the health of future children are receiving increased attention in popular media and in the academic press. In response, health profession organizations are developing clinical practice guidelines for warning pregnant women about the risks associated with exposures to certain toxics. We evaluate different sides of a risk-avoidance approach for pregnant women in the context of a hypothetical case study involving phthalates and women who work in nail salons. We consider the ubiquitous nature of low-dose exposures and both the positive aspects and limitations of promoting avoidance measures with respect to phthalate exposures. We conclude that a risk-disclosure approach has both practical limitations and equity dimensions which must be factored in to public health guidelines and messaging and the development of clinical practice guidelines. Upstream solutions including regulatory action on chemicals and heightened attention to environmental justice would result in optimal management of this issue.